Photonic monitoring of treatment during infection and sepsis: development of new detection strategies and potential clinical applications - Tannert, Astrid; Ramoji, Anuradha; Neugebauer, Ute; Popp, Juergen (Analytical and Bioanalytical Chemistry, 2018)
Despite the strong decline in the infection-associated mortality since the development of the first antibiotics, infectious diseases are still a major cause of death in the world. With the rising number of antibiotic-resistant pathogens, the incidence of deaths caused by infections may increase strongly in the future. Survival rates in sepsis, which occurs when body response to infections becomes uncontrolled, are still very poor if an adequate therapy is not initiated immediately. Therefore, approaches to monitor the treatment efficacy are crucially needed to adapt therapeutic strategies according to the patient’s response. An increasing number of photonic technologies are being considered for diagnostic purpose and monitoring of therapeutic response; however many of these strategies have not been introduced into clinical routine, yet. Here, we review photonic strategies to monitor response to treatment in patients with infectious disease, sepsis, and septic shock. We also include some selected approaches for the development of new drugs in animal models as well as new monitoring strategies which might be applicable to evaluate treatment response in humans in the future. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-20
Keywords: Antibiotic susceptibility testing; Imaging infection; Indocyanine clearance; Microcirculation imaging; Therapeutic drug monitoring; Treatment response